An Empirical Investigation on the Understandability of Accounting Income - Al-Adeem, Khalid; Al-Hassan, Hessah (Journal of Accounting and Finance, 2023)
This study surveys ninety-four well-educated and experienced accountants and individuals with mostly decent knowledge of accounting, some of whom own shares. Concerning findings are reported. The majority of participants generally do not comprehend that accounting income has no empirical reference, leading some to reveal the possibility of proving it. This understanding of the nature of accounting income partnered with a general agreement that different accountants can reach an exact accounting income for the same reporting entity when the same accounting standards are applied. Moreover, participants mostly demonstrate a sound understanding that calculating accounting income depends on both professional judgments applied to the implementation of financial accounting standards and on estimates involved in calculating accounting income. Comprehending such a nature, they articulate that accounting income is manipulatable whether for ethical or unethical purposes. Still, they rely on accounting income in making investment decisions. The Capital Market Authority should launch a campaign to educate individual investors about the nature and the limitation of such a figure.